2005
DOI: 10.1152/ajpendo.00591.2004
|View full text |Cite
|
Sign up to set email alerts
|

Indinavir alters regulators of protein anabolism and catabolism in skeletal muscle

Abstract: -The HIV protease inhibitor indinavir adversely impairs carbohydrate and lipid metabolism, whereas its influence on protein metabolism under in vivo conditions remains unknown. The present study tested the hypothesis that indinavir also decreases basal protein synthesis and impairs the anabolic response to insulin in skeletal muscle. Indinavir was infused intravenously for 4 h into conscious rats, at which time the homeostasis model assessment of insulin resistance was increased. Indinavir decreased muscle pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
(95 reference statements)
1
9
0
Order By: Relevance
“…This finding is in agreement with previous cell culture and animals studies in which EtOH or Ind treatment decreased protein synthesis in skeletal, cardiac, and smooth muscle cells (Hong-Brown et al, 2004, 2005bPreedy et al, 1990;Reilly et al, 1997). In contrast, Janneh et al (2003) reported that Ind did not impair preadipocyte protein synthesis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is in agreement with previous cell culture and animals studies in which EtOH or Ind treatment decreased protein synthesis in skeletal, cardiac, and smooth muscle cells (Hong-Brown et al, 2004, 2005bPreedy et al, 1990;Reilly et al, 1997). In contrast, Janneh et al (2003) reported that Ind did not impair preadipocyte protein synthesis.…”
Section: Discussionsupporting
confidence: 92%
“…Paradoxically, treatment with HIV-protease inhibitors (PIs) as part of the highly active antiretroviral therapy (HAART) also causes metabolic disorders, even though HAART markedly reduces the morbidity and mortality in this patient population (Palella et al, 1998). Metabolic derangements associated with PI treatments include changes in protein metabolism, dyslipidemia, central adiposity, and peripheral lipodystrophy (Carr et al, 1998;Hong-Brown et al, 2005b). Likewise, several studies reported that PIs impair insulin-mediated glucose uptake by adipose and muscle tissues, resulting in a diabetic-like condition (Murata et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were cultured in Dulbecco's modified Eagle's medium containing 10% FBS, penicillin (100 units/ml), streptomycin (100 g/ml), and amphotericin (25 g/ml). Experiments were conducted using cells at the myotube stage in which 80 mM ethanol was added to cells, exactly as previously described (19,20). Cells were pulse-labeled with [ 35 S]-methionine/ cysteine in the presence or absence of alcohol for various times to determine the rate of degradation.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, whereas the introduction of highly active antiretroviral therapy (HAART) has limited involuntary weight loss, a significant number of AIDS patients still manifest muscle wasting (46,56), especially as the severity of the disease progresses (5,53). However, investigation of the effects of HIV-1 infection under controlled conditions in humans is complicated by recurrent opportunistic bacterial infections and the pharmacological side effects of HAART, each of which can negatively impact muscle protein balance (15,24). Although the pathogenesis of HIV-induced wasting is multifactorial, where a reduction in energy intake and/or malabsorption is clearly contributory (12,30), the etiology of the metabolic defect is poorly characterized.…”
mentioning
confidence: 99%